Current developments in biotechnology and bioengineering : sustainable food waste management : resource recovery and treatment - Wong, Jonathan W. C.; Kaur, Guneet, 1985-; Taherzadeh, Mohammad; Pandey, Ashok; Lasaridi, Katia (Elsevier, 2021)
Current Developments in Biotechnology and Bioengineering: Sustainable Food Waste Management: Resource Recovery and Treatment covers the latest methods of food waste management and resource recovery from a sustainability perspective and is suitable for universities, municipalities, and companies working in the field. This book provides a comprehensive account of food waste chemistry, the latest techniques for food waste treatment and recycling, sustainability assessment (social, economic, environmental), and challenges in food waste management. The book explores recycling to value-added products using sustainable concepts and methodologies, and is useful as a course or reference book for biochemical engineering, environmental sustainability, and waste management.